Simon Kirene dan Teologi Empati: Kajian Pastoral tentang Solidaritas di Tengah Derita - Budiman Siregar; Yosef Antonius; Kornelius Rulli Jonathans (STTI Harvest Semarang, 2025)
The story of Simon of Cyrene being compelled to carry Jesus’ cross (Luke 23:26) is often read as a peripheral narrative within the Passion account. However, from a pastoral theological perspective, Simon’s figure represents a profound act of empathy and an actualization of solidarity in suffering. This article aims to highlight the pastoral significance of Simon of Cyrene’s action as a paradigm of empathy in pastoral ministry. Through a pastoral hermeneutical approach and biblical narrative analysis, the study elaborates how Simon’s action reflects an active presence amid the suffering of others, even without prior preparation or willingness. This context is highly relevant for contemporary pastoral care, especially in accompanying individuals or communities experiencing trauma, crisis, or marginalization. The theology of empathy derived from Simon’s story challenges pastoral ministers to embody real solidarity—not merely through words of consolation, but through concrete involvement in bearing the burdens of others. The article also emphasizes the importance of pastoral readiness to become “contemporary Simons,” present not because of position or authority, but out of a heartfelt calling to compassionate accompaniment. Thus, the story of Simon of Cyrene serves as a reflective mirror for a humanistic, responsive, and transformative model of pastoral ministry amidst the realities of suffering in today’s world. AbstrakKisah Simon dari Kirene yang dipaksa untuk memikul salib Yesus (Lukas 23:26) sering kali dibaca sebagai narasi sampingan dalam sengsara Kristus. Namun, dari perspektif teologi pastoral, figur Simon justru merepresentasikan tindakan empatik yang mendalam dan aktualisasi solidaritas dalam penderitaan. Artikel ini bertujuan untuk mengangkat makna pastoral dari tindakan Simon Kirene sebagai paradigma empati dalam pelayanan pastoral. Melalui pendekatan hermeneutika pastoral dan telaah naratif biblika, kajian ini mengelaborasi bagaimana tindakan Simon mencerminkan kehadiran aktif di tengah penderitaan orang lain, sekalipun tanpa persiapan atau kerelaan awal. Konteks tersebut relevan bagi pelayanan pastoral masa kini, terutama dalam mendampingi individu atau komunitas yang mengalami trauma, krisis, atau marginalisasi. Teologi empati yang digali dari kisah Simon menantang para pelayan pastoral untuk menghadirkan solidaritas yang nyata, bukan hanya melalui kata-kata penghiburan, tetapi melalui keterlibatan konkret dalam memikul beban sesama. Artikel ini juga menyoroti pentingnya kesiapsediaan pastoral untuk menjadi